Crop Diversity and Farmers’ Livelihood in an Agriculturally Prosperous District of West Bengal - Debkumar Kisku; Souvik Ghosh (Indian Journal of Extension Education, 2017)
The present study highlights the impact of crop diversification on livelihood security and level of living of the farmers in an agriculturally prosperous district of West Bengal. A total of seven different cropping patterns were followed by the farmers, where 13 out of 120 farmers adopted more than one cropping pattern. The cropping pattern of Paddy-PotatoSesame was preferred by most of the farmers (56.39%). The impact of crop diversification on livelihood security was measured on the basis of six indicators, each on 5-point continuum. The perception of livelihood security of all the groups of farmers was found at above average level (≥15) ranging from 16.26 to 18.38 except group of six farmers following Paddy-Fallow-Paddy cropping pattern. The level of living indicated through five types of assets holdings of the groups of farmers adopting various cropping pattern, each of which measured on 5-point continuum. Level of living was found to be below average (≤12.50) for all the groups ranging from 12.39 to 10.32, lowest for group of farmers following PaddyFallow-Paddy cropping pattern. Therefore, it is worth mentioning that the crop diversity is a key to the livelihood security. The change in level of living is a gradual process and also depends on initial level of resources/assets of farmers.